Paved with good intentions the American experience and Iran - Rubin, Barry M. (New York Oxford University Press, 1980)
A history of United States and Iranian relations over the past quarter of a century.
A friendship is born -- A country is saved 1945-50 -- A revolution is overthrown 1951-53 -- An alliance is made 1954-68 -- An imperial dream 1969-74 -- Arms and the shah 1975-76 -- The pillar crumbles 1977-78 -- Days of reckoning 1978-79 -- Charismatic disorder 1979 -- Iran's second revolution 1979-80.
Includes bibliographical references (pages 402-416) and index.
Keywords: United States -- Foreign relations -- Iran; Iran -- Foreign relations -- United States